Using students' misconceptions of primary coloured lights to design a hands-on coloured light mixer - Suchai Nopparatjamjomras (2018)
A surface mount typed multi-coloured Light-Emitting Diode (LED) is used as a light source for the hands-on coloured light mixer. The LED consists of red, green and blue tiny sources but the mixer is designed to have four switches corresponding to red, green, blue and yellow light. These colours correspond to students' misconceptions of primary coloured lights; they realize that the primary colours and the rules for lights mixing are the same as those of paints. To generate a yellow light, a microcontroller placed between four input switches and the LED operates both a red and green tiny sources. In addition, the microcontroller is employed to eliminate some combinations of coloured light mixing to simplify the experiment (basic mode) for non advanced students. If the mixer is used with more advanced students, a number of combinations will increase and students need more analytical skills to find out the primary coloured lights (the coloured lights that can not be produced by the mixing of any other coloured lights). Therefore, the mixer is able to use with more advanced and non advanced students depending on the program in the microcontroller and some modifications of the circuit. Furthermore, to introduce students an idea that other hues or shades can be generated by mixing of these three primary coloured lights of different intensities, a tuning circuit is integrated to vary an intensity of the green light source. © ETOP 2009.